Development of salt tolerant lines in Mung bean (Vigna radiata L. Wilczek Var. - K – 851) (International Journal of Scientific Research in Science and Technology, 2026)
Different ex plants such as hypocotyls, excised roots, steam segments, cotyledons, first leaf, secondary leaf, shoot apices of mung bean [Vigna radiata (L.) Wilczek] variety K 851 were inoculated on MS (Murashige and Skoog, 1962) medium supplemented with different concentrations of various hormones, viz. indoleacetic acid (IAA), -2, 4-dichlorophenoxyacetic acid (2, 4-D), naphthaleneacetic acid (NAA), 6-benzyladenine (BA) and kinetin (KN) fortified with NaCl (0.25, 0.50, 0.75 and 1.00% concentration). Salt stress showed decreased germination with increasing salt concentrations. MS media supplemented with 2, 4-D) and B.A. showed morphogenesis at various salt concentrations, some salt tolerant explants were isolated and regeneration of shoots have been achieved at 5 μM BA + 1 μM NAA, but an alteration in leaf morphology was noted. Rooting have been induced in such regenerants at 20 μM NAA without intervening callus phase. These plantlets were transferred to Knop’s solution for hardening. Later they were transferred to pots with autoclaved soil.